Targeting of bone morphogenetic protein complexes to heparin/heparan sulfate glycosaminoglycans in bioactive conformation. Issue 1 (23rd December 2022) - Spanou, Chara E. S.; Wohl, Alexander P.; Doherr, Sandra; Correns, Annkatrin; Sonntag, Niklas; Lütke, Steffen; Mörgelin, Matthias; Imhof, Thomas; Gebauer, Jan M.; Baumann, Ulrich; Grobe, Kay; Koch, Manuel; et al.
Abstract: Bone morphogenetic proteins (BMP) are powerful regulators of cellular processes such as proliferation, differentiation, and apoptosis. However, the specific molecular requirements controlling the bioavailability of BMPs in the extracellular matrix (ECM) are not yet fully understood. Our previous work showed that BMPs are targeted to the ECM as growth factor‐prodomain (GF‐PD) complexes (CPLXs) via specific interactions of their PDs. We showed that BMP‐7 PD binding to the extracellular microfibril component fibrillin‐1 renders the CPLXs from an open, bioactive V‐shape into a closed, latent ring shape. Here, we show that specific PD interactions with heparin/heparan sulfate glycosaminoglycans (GAGs) allow to target and spatially concentrate BMP‐7 and BMP‐9 CPLXs in bioactive V‐shape conformation. However, targeting to GAGs may be BMP specific, since BMP‐10 GF and CPLX do not interact with heparin. Bioactivity assays on solid phase in combination with interaction studies showed that the BMP‐7 PD protects the BMP‐7 GF from inactivation by heparin. By using transmission electron microscopy, molecular docking, and site‐directed mutagenesis, we determined the BMP‐7 PD‐binding site for heparin. Further, fine‐mapping of the fibrillin‐1‐binding site within the BMP‐7 PD and molecular modeling showed that both binding sites are mutually exclusive in the open V‐ versus closed ring‐shape conformation. Together, our data suggest that targeting exquisite BMP PD‐binding sites by extracellular protein and GAG scaffolds integrates BMP GF bioavailability in a contextual manner in development, postnatal life, and connective tissue disease.